If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18=-5-(6k-19)
We move all terms to the left:
-18-(-5-(6k-19))=0
We calculate terms in parentheses: -(-5-(6k-19)), so:We get rid of parentheses
-5-(6k-19)
determiningTheFunctionDomain -(6k-19)-5
We get rid of parentheses
-6k+19-5
We add all the numbers together, and all the variables
-6k+14
Back to the equation:
-(-6k+14)
6k-14-18=0
We add all the numbers together, and all the variables
6k-32=0
We move all terms containing k to the left, all other terms to the right
6k=32
k=32/6
k=5+1/3
| y+2y=2 | | 3+6s=4(s-12)+19 | | 4x+7=15+0 | | 4x+7=15=0 | | (3x-3=4x+1,x) | | 2x+32/5=5x-4/5 | | 2=-0.01x | | N+3n=188 | | H=8(4b)^2+2 | | 2x+1/4=-3/4x | | (5x+11=x-5,x) | | 10x+23=17x-37 | | X+19=-2x | | 9x=10x+7 | | 5x+11=x-5,x | | (X+4)x=165 | | 18-0.33x=-7 | | 20x-3=17x-36 | | 2/3+n=7/3 | | 6*14=n | | 5(3x+12)-9=6 | | 16w=6+40 | | 16w=16+40 | | 2.1n-531=18 | | x/3+x+20=180 | | y=183 | | -5(w+3)=-5w+1 | | -4/5(x-1/4)=3/7 | | 1/2(-4x+8)=-40 | | 6x+11=-2-8 | | 3y+(4y-40)=180 | | 1x+11=-2-8 |